Individual Characteristics and Workload Related to The Symptoms of Sick Building Syndrome on Employees of PT. Infomedia Nusantara in 2020 - Chotimah, Aulia Nursyafitiri (Health Safety Environment, 2020)
Background: Over the past few years, the term Sick Building Syndrome has become more common but not everyone is clear about what it is. Sick Building Syndrome is described as a situation where more than 20% of building occupants complain about air quality or have persistent symptoms. Elsewhere, such as in major cities in Indonesia, the possibility of Sick Building Syndrome is high because there are many building constructions without considering health factors. This study aimed to determine the relationship between individual characteristics and workload with Sick Building Syndrome symptoms on employees of PT. Infomedia Nusantara in 2020. Methods: Sample selection technique by total sampling and a sample size of 72 respondents using the cross-sectional method. Data collection using questionnaire aids. The results of data collection will be analyzed univariate and bivariate. Results: The results revealed that there was a relationship between age (p = 0.029), psychosocial condition (p = 0041), and job stress (p = 0.021) with Sick Building Syndrome symptoms. Conclusions: respondents who had experienced Sick Building Syndrome symptoms had a significant association between age, psychosocial conditions, and work stress.Keywords: Sick Building Syndrome, individual characteristics, employee, office